Analysis of UK river restoration using broad‐scale data sets. (11th November 2013) - Smith, Benjamin; Clifford, Nicholas J.; Mant, Jenny
Abstract This paper uses data from the UK River Restoration Centre's National River Restoration Inventory (NRRI) and the UK Environment Agency's River Habitat Survey (RHS) to analyse the relationship between restoration technique and the physical catchment context in which they have been implemented. Specifically we tested the relationship between categories of restoration technique and energy conditions, the relationship between restoration project and degree of channel modification, and whether the associations between restoration and physical catchment attributes have changed over time. Significant associations between categories of restoration technique and catchment variables were found, with direct morphological interventions needed in lower energy conditions; however, the analysis shows no change over time. This work shows that analysis of existing data sets can provide useful information to support the science and practice of river restoration and suggests that further analysis of existing ecological and geomorphological data sets provides an important learning opportunity to strengthen river restoration.